Implementasi SK Rektor Universitas Sumatera Utara Nomor: 2132 Tahun 2024 Tentang Pengangkatan Dosen Tidak Tetap Pada Fakultas Ekonomi dan Bisnis USU - Dian Novita Sari; Indra Muda (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study analyzes the implementation of USU Rector's Decree No. 2132 of 2024 concerning the Appointment of Non-Permanent Lecturers at the Faculty of Economics and Business, University of North Sumatra (FEB USU). This policy aims to overcome the deficit of teaching staff and improve the quality of education at FEB USU. A descriptive qualitative approach is used in this study, with in-depth interviews, observation, and document analysis methods. The data was analysed using the policy implementation models of Van Meter & Van Horn and Edward III, which highlighted aspects of communication, resources, executive disposition, and bureaucratic structure. The results of the study show that policy communication is effective, supported by good coordination between faculty leaders, study programs, and teaching staff. However, there are several challenges, such as the age and health of lecturers are not fixed, budget limitations, a lack of synchronization in the delivery of teaching materials, and the high workload of lecturers. Therefore, a strategy to improve academic coordination, budget optimization, and a better evaluation system is needed to ensure the sustainability and effectiveness of this policy in improving the quality of education at FEB USU.